Effectiveness of Arbuscular Mycorrhiza and Slow Release Fertilizer to the Growth of Merawan Siput Jantan (Hopea Odorata Roxb.) - Hasan, Mohd Ghazali (2004)
Merawan siput jantan (Hopea odorata Roxb.) is a forest tree species that can be used for plantation establishment in marginal lands. Arbuscular Mycorrhiza (AM) and fertilizer are believed to have the ability to increase tree growth in the nursery and in the field. This study was conducted to determine the effectiveness of mycorrhiza and fertilizer application on the growth of merawan siput jantan in both conditions. The nursery study was conducted in FRIM’s nursery, Kepong. It was conducted to determine the optimum level of AM inoculation and fertilizer application required for maximum tree growth. The merawan siput jantan seedlings were inoculated with three levels of AM (Draz-M) inoculation viz; 0, 100 and 200 g per seedling. The levels of nutrient (Vitality/ slow release fertilizer) were applied in four different amount viz; 0, 5, 10 and 20 g per seedling. Results of the study showed that inoculation using 100 g per seedling had given the highest increment of height and diameter, 6 months after the treatment. It was found that, application of AM alone did not contribute on the tree growth because the AM acts as biological booster rather than supplying nutrients. However, based on the analysis, it was found that height increment had been significantly increased by application of both AM and fertilizer compared to fertilization alone due to their synergistic interaction. A field study to evaluate application of AM and fertilizer had been conducted at plantation areas in LKPP Sg. Charu, Kuantan, Pahang. It was conducted by applying inoculated AM and fertilizer to merawan siput jantan trees in Block A: 8 months after planting and Block B: 14 months after planting. The trees were treated with two different levels of AM viz; 0 and 500 g tree-1, and three different levels of fertilizer viz; 0, 250 and 500 g tree-1. Results of the field study had further supported results of nursery study that AM had contributed on the tree growth. It was found that, application of slow release fertilizer (NPK 10:7:7) at 500 g tree-1 had significantly increased (P<0.001) the height of merawan siput jantan in both blocks. The growth of tree canopy also showed similar result.Application of slow release fertilizer indicated increased nutrients in the soil especially P and Mg at the end of the experiment. The effects of AM and fertilizer application can be observed after one year of treatments viz; i. The AM inoculated plot especially incorporated with fertilizer had increased Ca content in leaves while N is found increased in stem. ii. Contents of K and Mg in roots were also increased due to the fertilizer application. It shows that AM is able to increase nutrient absorption by the roots of the trees through symbiosis. iii. Results from nursery and field studies showed that application of AM and fertilizer have positively contributed to the tree growth. Therefore, it is recommended that the AM and fertilizer should be applied to trees both in nursery an in the field as they have been proven to improve growth.